A premature luteinizing hormone surge without elevated progesterone levels has no adverse effect on cumulative live birth rate in patient undergoing a flexible GnRH antagonist protocol: a retrospective study - Yangyang Zhang; Yang Xu; Jiao Yu; Xi Wang; Qing Xue; Jing Shang; Xiuli Yang; Xuemin Shan (BMC, 2023)
Abstract Background A premature luteinizing hormone (LH) surge refers to an endogenous LH peak that occurs before follicle maturation or human chorionic gonadotropin injection in the process of controlled ovarian hyperstimulation. The effect of premature LH surge on pregnancy outcomes in fresh embryo transfer cycles is still controversial. The aim of this study was to explore the effect of a premature LH surge without elevated progesterone levels on the cumulative pregnancy rate (CPR) and cumulative live birth rate (CLBR) of patients during a flexible GnRH antagonist protocol. Methods A total of 730 infertile women undergoing IVF/ICSI were recruited for this retrospective study. Only women who either delivered a live infant or had no remaining frozen embryos after a single stimulation cycle were included in the analysis. During the study period, each patient underwent a flexible GnRH antagonist protocol. Women were divided into two groups according to the presence or absence of a premature LH surge. The primary outcome measures were the CPR and CLBR per ovarian stimulation cycle. The secondary outcome measures were the number of oocytes retrieved, fertilization rate, good-quality embryo rate, and clinical pregnancy rate. Results Ninety-one women (12.47%) experienced a premature LH surge without elevated progesterone levels, and the other 639 (87.53%) women were assigned to the control group. The numbers of oocytes retrieved and fertilization rate were significantly greater in the premature LH surge group than in the control group. There was no significant difference between groups in the good-quality embryo rate, clinical pregnancy rate or live birth rate in the fresh embryo transfer cycle. The primary outcome measures, the CPR and CLBR per ovarian stimulation cycle, were not significantly different between the premature LH surge group and the control group. According to the analysis stratified by ovarian response (normal or high), there were no significant differences in pregnancy outcomes between the groups with and without a premature LH surge. Conclusions The retrospective study demonstrated that the patients experiencing a transient premature LH surge without progesterone elevation had equivalent pregnancy outcomes with those without a premature LH surge on a flexible GnRH antagonist protocol. The present conclusions need to be further validated in a prospective well-designed large-scale study.